Insuficiencia Jurídica Respecto De La Regulación De Los Contratos De Servicio Civiles Ocasionales” - Culquicondor Campoverde, Geovanny Tomás (2016)
The Public Service Law allows civil contracts in the form of occasional services or professional civil contracts, but these alone are mentioned in Section 6 in relation to nepotism and in Article 48 literal k) as grounds for removal of a server. For these circumstances the Public Service Law allows civil service contracts, but there is no provision regulates the way of carrying out these contracts, an issue that if regulated when it comes to occasional service contracts in the Article 148 of Regulation General of the Public Service Law, an issue that is illegal for contravening the hierarchy of norms, for according to it, the regulation would be above the law. Its standardization of Law Public Service guarantee as stated in Article 229 of the Constitution of the Republic of Ecuador, that the law is responsible for defining the lead agency for human resources and remuneration for all public sector and regulate the entry, advancement, promotion, incentives, Discipline, stability, system of remuneration and termination of appointment of its servers. Because of the circumstances listed, because the General Regulation of the Public Service Law regulates professional service contracts and Public Service Law does not, then contrasts the merits of the substantive law on the rights and duties develops, generating legal uncertainty of public institutions. For the legal basis, it becomes essential that the Public Service Law to normal occasional service contracts under the law of legal persons and natural persons the mandatory application of the public procurement rules.